Questionário para Avaliação de Qualidade de Vida em Portadores de Doença Hepática Crônica: Tradução e Validação do CLDQ – Chronic Liver Disease Questionnaire - Mucci, Samantha [UNIFESP] (2009)
The aim of this study was to carry out the translation from English into Portuguese and the transcultural adaptation of the Chronic Liver Disease Questionnaire to use in Brazil. The instrument was translated from the original version (English) into Portuguese language by the authors and then, it was revised. The degree of difficulty of the translations and equivalence for bilingual translators were evaluated. The instrument was, then, applied in 20 patients with chronic liver disease randomly selected. It was easy to the patients understand the instrument, all the questions had been considered applicable by the patients, and the cultural equivalence of the CLDQ was demonstrated without changes in the original translation. The translation and the transcultural adaptation of CLDQ into Portuguese, in Brazil, had been carried out, having been fulfilled to this important stage for its validation and use in our way.